MOFs and porous carbon composite material and preparation method and application thereof
By combining ZIF-8 with porous carbon, MOFs and porous carbon composites with highly ordered pore structures were prepared, which solved the problems of low adsorption amount and poor selectivity in the existing CO2 capture technology, and achieved efficient, stable and economical CO2 capture effect.
Patent Information
- Application Number
- CN202311389424.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-25
AI Technical Summary
The existing CO2 capture technology has problems of low adsorption amount and poor selectivity, which limits its popularity and promotion in industrial applications.
Using MOFs and porous carbon composite materials, a composite material with a highly ordered pore structure and good chemical stability was prepared by combining the metal organic frame material ZIF-8 with porous carbon. The method includes heat treatment of mixed metal organic frame material and porous carbon precursor and surface modification treatment.
It achieves high CO2 adsorption and selectivity, has recyclability, high stability and low operating costs, and is suitable for industrial mass production.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of novel composite materials, and in particular to a MOFs and porous carbon composite material and a preparation method and application thereof. Background Art
[0002] Industrial combustion and other high-temperature processes release large amounts of carbon dioxide, which accumulates excessively in the atmosphere, exacerbating the greenhouse effect. Therefore, it is urgent to develop efficient carbon dioxide capture technology.
[0003] At present, traditional CO2 capture technologies mainly include absorption-desorption, membrane separation and chemical absorption, etc. However, these technologies have disadvantages such as high cost, complex operation, high energy consumption and poor CO2 selectivity, which limits their popularization and promotion in industrial applications.
[0004] Metal organic frameworks (MOFs) are considered to be the most promising adsorption materials, with high CO2 adsorption capacity under high pressure, but they have problems such as low adsorption capacity at normal pressure and low selectivity. Porous carbon materials have come into people's attention due to their advantages such as light weight, strong thermal stability and low price, but their selectivity for CO2 adsorption is poor, and the preparation process of porous carbon with high specific surface area is complicated.
[0005] Therefore, the research and development of new high-adsorption materials has important practical significance and research value for CO2 adsorption. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of low adsorption capacity and poor adsorption selectivity of adsorbent materials when the adsorbent materials are used to capture CO2 in the prior art, and to provide a MOFs and porous carbon composite material and a preparation method and application thereof. The MOFs and porous carbon composite material prepared by the method provided by the present invention have a highly ordered pore structure and good chemical stability, can capture CO2 in flue gas, and have high CO2 adsorption and selectivity, and have the advantages of recyclability, high stability, etc.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a MOFs and porous carbon composite material, wherein the composite material includes a metal organic framework material and porous carbon combined in the metal organic framework material; the metal organic framework material is ZIF-8; the mass ratio of the metal organic framework material to the porous carbon is 1:0.5-2.
[0008] A second aspect of the present invention provides a method for preparing a MOFs and porous carbon composite material, the method comprising:
[0009] (1) mixing a metal organic framework material and a porous carbon precursor to obtain a mixed material;
[0010] (2) heat treating the mixed material to obtain a MOFs and porous carbon composite;
[0011] (3) The composite is subjected to surface modification treatment to obtain a MOFs and porous carbon composite material.
[0012] The third aspect of the present invention provides a MOFs and porous carbon composite material prepared by the method described in the second aspect.
[0013] The fourth aspect of the present invention provides an application of the MOFs and porous carbon composite material described in the first aspect or the third aspect in the technology of capturing carbon dioxide in flue gas.
[0014] Through the above technical solution, the present invention can achieve the following technical effects:
[0015] (1) The present invention uses MOFs and porous carbon precursors as raw materials to prepare MOFs and porous carbon composite materials. Since MOFs have a highly ordered pore structure and micropores of precise size and shape, and can produce good synergistic effects with porous carbon, the prepared composite material exhibits a large adsorption capacity.
[0016] (2) The MOFs and porous carbon composite materials provided by the present invention are prepared by adding MOFs and porous carbon precursors simultaneously. The obtained composite materials have a smaller pore size and a higher specific surface area. After multiple adsorption and regeneration, they can still maintain a highly ordered pore structure and have high stability and recyclability.
[0017] (3) The MOFs and porous carbon composite materials provided by the present invention, by introducing porous carbon, are combined with MOFs in the form of carbon materials during the heat treatment process to form a porous structure, which can not only give the composite material additional pore structure and surface area, but also enhance the adsorption and selectivity of CO2.
[0018] (4) The MOFs and porous carbon composite materials provided by the present invention are suitable for capturing CO2 in flue gas at higher temperatures, and the method is simple, easy to operate, and has low operating costs, and can be used for industrial mass production. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The first aspect of the present invention provides a MOFs and porous carbon composite material, wherein the composite material includes a metal organic framework material and porous carbon combined in the metal organic framework material; the metal organic framework material is ZIF-8; the mass ratio of the metal organic framework material to the porous carbon is 1:0.5-2.
[0021] In the present invention, the composite material is composed of a metal organic framework material and porous carbon combined in the metal organic framework material. The metal organic framework material has a highly ordered pore structure. By introducing porous carbon, it is combined with MOFs in the form of a carbon material. The morphology and structure of the obtained composite material are not particularly limited. The MOFs particles and the porous carbon precursor particles in the composite material can exist in the form of contact, coating or embedding. Compared with the MOFs material, the composite material has more pores, a larger specific surface area and more active sites. After multiple adsorption and regeneration, it still has a highly ordered pore structure and will not be significantly damaged or inactivated. It has high stability and recyclability, can be used for the capture of CO2 in flue gas at higher temperatures, and has more efficient adsorption and selectivity.
[0022] In the present invention, the mass ratio of the metal organic framework material to the porous carbon is 1:0.5-2, which can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 and any value in the range formed by any two of these point values. Meeting this range is conducive to making the composite material have more efficient adsorption and selectivity in the CO2 adsorption process, and has higher stability and recyclability.
[0023] In some embodiments of the present invention, preferably, the average pore size of the composite material is 0.2-0.5 nm, and the specific surface area is 800-1200 m 2 In the present invention, the specific surface area of the composite material is measured by nitrogen adsorption method (BET method); and the average pore size is measured by pore size distribution analyzer.
[0024] In some embodiments of the present invention, preferably, the composite material further contains a modified functional group attached to the metal organic framework material and the porous carbon surface; the modified functional group is selected from at least one of a hydroxyl group, an amino group and a carbonyl group.
[0025] In some embodiments of the present invention, preferably, in the composite material, the content of the modified functional group is 0.1-0.5 wt %.
[0026] In the present invention, the surface of the composite is modified to increase the hydroxyl, carboxyl and alkaline groups on the surface of the composite, which is beneficial to improving the chemical reaction activity of the composite surface and improving the adsorption performance and selectivity of CO2.
[0027] In some embodiments of the present invention, preferably, the pore size of ZIF-8 is 0.34-0.36 nm, the average particle size is 10-100 nm, and the specific surface area is 1200-1600 m 2 / g.
[0028] In the present invention, the pore size, average particle size, and specific surface area of the ZIF-8 material are controlled within the above ranges, which is conducive to making the composite material have more efficient adsorption and selectivity in the CO2 adsorption process, and has higher stability and recyclability. In addition, in the present invention, the ZIF-8 material has a specific crystal structure, in which metal ions and organic ligands are composed in a precise proportion and arrangement, giving the ZIF-8 material a highly ordered pore structure, which can be obtained commercially, for example, from Shanghai Chuangsai Technology Co., Ltd.
[0029] The second aspect of the present invention provides a method for preparing a MOFs and porous carbon composite material, characterized in that the method comprises:
[0030] (1) mixing a metal organic framework material and a porous carbon precursor to obtain a mixed material;
[0031] (2) heat treating the mixed material to obtain a MOFs and porous carbon composite;
[0032] (3) The composite is subjected to surface modification treatment to obtain a MOFs and porous carbon composite material.
[0033] In some embodiments of the present invention, preferably, in step (1), the mass ratio of the metal organic framework material to the porous carbon precursor is 1:0.5-2.
[0034] In the present invention, by regulating the mass ratio of MOFs material and porous carbon precursor, it is beneficial to make the composite material have more efficient adsorption and selectivity in the CO2 adsorption process, and have higher stability and recyclability.
[0035] In some embodiments of the present invention, preferably, in step (1), the porous carbon precursor is polystyrene; and the weight average molecular weight of the polystyrene is 30000-80000 g / mol.
[0036] In the present invention, in step (1), the porous carbon precursor is polystyrene, preferably solid polystyrene particles, and its form is not particularly limited as long as it can be combined with the MOFs material in the form of a carbon material, for example, it can be granular, micropowdered, or spherical; the diameter of the polystyrene is 50-1000nm. In addition, polystyrene can be purchased commercially, for example, it can be purchased from Hubei Yunmei Technology Co., Ltd.
[0037] In some embodiments of the present invention, preferably, the metal organic framework material is ZIF-8; the pore size of ZIF-8 is 0.34-0.36 nm, the average particle size is 10-100 nm, and the specific surface area is 1200-1600 m 2 In the present invention, the description of ZIF-8 is as mentioned above and will not be repeated here.
[0038] In some embodiments of the present invention, preferably, in step (2), the heat treatment is carried out in the presence of a protective gas, and the protective gas is preferably nitrogen, and the nitrogen gas flow rate is 50-80 mL / min; the target temperature of the heat treatment is 400-600°C, and the holding time is 2-6 h, preferably 3-5 h.
[0039] In the present invention, the heat treatment process causes part of the carbon atoms of the porous carbon material to be gasified, thereby gradually forming a developed pore structure, which can improve the material's ability to adsorb gas.
[0040] In the present invention, the flow rate of the inert gas during the heat treatment process needs to be strictly controlled within the above range, which is conducive to ensuring that the inert atmosphere can effectively cover the surface of the material and maintain a stable atmosphere environment. If the flow rate is too low, the atmosphere may be uneven and the material cannot be effectively protected; if the flow rate is too high, the atmosphere may be disturbed or the material particles may be lost.
[0041] In the present invention, the target temperature and treatment time of the heat treatment are controlled within the above range, which is conducive to making the composite material have a highly ordered pore structure, with more efficient adsorption and selectivity. If the target temperature is too low, the expected treatment effect cannot be achieved, and if the temperature is too high, the structure will be destroyed, causing the collapse of the pores, which is not conducive to the adsorption of gas; in addition, if the heat treatment time is too short, the expected effect of optimizing the pore structure of the porous carbon material cannot be achieved, and if the time is too long, the material yield will be low, the skeleton will easily collapse, and the porous morphology cannot be well maintained.
[0042] According to some embodiments of the present invention, preferably, in step (3), the surface modification process comprises: keeping the composite at the target temperature for 2-5 hours in the presence of hydrofluoric acid or a mixed gas containing ammonia; the concentration of the hydrofluoric acid is 10-20wt%; the mixed gas comprises ammonia and nitrogen; and the concentration of ammonia in the mixed gas is 0.5-1wt%.
[0043] In the present invention, the introduction of hydrofluoric acid increases the hydroxyl and carboxyl content on the surface of the composite, and the introduction of a mixed gas containing ammonia introduces basic groups on the surface of the composite to enhance the chemical reaction activity of the composite surface and improve the adsorption and selectivity of CO2. In addition, in the present invention, ammonia provides a large number of Lewis basic sites, which is conducive to the adsorption of CO2 (acidic gas molecules), but has no obvious effect on N2, thereby improving the selectivity of the composite material; and the preparation method is simple, has low equipment requirements, and can be used for industrial mass production.
[0044] The third aspect of the present invention provides a MOFs and porous carbon composite material prepared by the method described in the second aspect.
[0045] The fourth aspect of the present invention provides an application of the MOFs and porous carbon composite material described in the first aspect or the third aspect in the technology of capturing carbon dioxide in flue gas.
[0046] The present invention will be described in detail below through examples.
[0047] The specific surface area was determined by nitrogen adsorption method (BET method);
[0048] The average pore size is measured using a pore size distribution instrument (pore size distribution analyzer);
[0049] The amount of CO2 adsorbed was measured using a gas adsorption instrument (mass spectrometry under normal pressure).
[0050] Example 1
[0051] (1) 15 g of ZIF-8 and 15 g of polystyrene (weight average molecular weight of 50,000 g / mol) were mixed to obtain a mixed material;
[0052] (2) transferring the above mixed material to a high temperature furnace, performing heat treatment in a nitrogen atmosphere, controlling the nitrogen flow rate to 50 mL / min, raising the temperature to 500° C., and reacting at a constant temperature for 5 h to obtain a MOFs and porous carbon composite;
[0053] (3) The prepared composite was surface modified by introducing a mixed gas containing 1 wt% ammonia, and then kept warm at 500°C for 4 h and cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-1.
[0054] The BET of MOF-1 was determined to be 900m 2 / g, the average pore size is 0.4nm, and the content of the surface modified functional group amino group is 0.5wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-1 is 3.6mmol / g, and the CO2 selectivity is greater than 98%. After 10 cycles of testing, it still has good CO2 adsorption performance and selectivity.
[0055] Example 2
[0056] (1) mixing 10 g of ZIF-8 and 20 g of polystyrene (weight average molecular weight of 50,000 g / mol) to obtain a mixed material;
[0057] (2) transferring the above mixed material to a high temperature furnace, performing heat treatment under a nitrogen atmosphere, controlling the nitrogen flow rate to 50 mL / min, raising the temperature to 600° C., and reacting at a constant temperature for 3 h to obtain a MOFs and porous carbon composite;
[0058] (3) The prepared composite was surface modified by introducing a mixed gas containing 0.5 wt% ammonia, and then kept warm at 600°C for 3 h and cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-2.
[0059] The specific surface area of MOF-2 is 1200m 2 / g, the average pore size is 0.3nm, and the content of surface modified functional group amino is 0.4wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-2 is 3.5mmol / g, and the CO2 selectivity is greater than 98%.
[0060] Example 3
[0061] (1) 20 g of ZIF-8 and 10 g of polystyrene (weight average molecular weight of 50,000 g / mol) were mixed to obtain a mixed material;
[0062] (2) transferring the above mixed material to a high temperature furnace, performing heat treatment in a nitrogen atmosphere, controlling the nitrogen flow rate to 50 mL / min, raising the temperature to 500° C., and reacting at a constant temperature for 4 h to obtain a MOFs and porous carbon composite;
[0063] (3) The prepared composite was surface modified by introducing a mixed gas containing 0.5 wt% ammonia, and then kept warm at 500°C for 4 h and cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-3.
[0064] It has been determined that the specific surface area of MOF-3 is 700m2 / g, the average pore size is 0.4nm, and the content of surface modified functional group amino is 0.4wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-3 is 3.2mmol / g, and the CO2 selectivity is greater than 96%.
[0065] Example 4
[0066] (1) 15 g of ZIF-8 and 15 g of polystyrene (weight average molecular weight of 50,000 g / mol) were mixed to obtain a mixed material;
[0067] (2) transferring the above mixed material to a high temperature furnace, performing heat treatment in a nitrogen atmosphere, controlling the nitrogen flow rate to 50 mL / min, raising the temperature to 400° C., and reacting at a constant temperature for 6 h to obtain a MOFs and porous carbon composite;
[0068] (3) The prepared composite was surface modified by introducing a mixed gas containing 0.5 wt% ammonia, and then kept warm at 400°C for 4 hours and then cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-4.
[0069] It has been determined that the specific surface area of MOF-4 is 1000m 2 / g, the average pore size is 0.4nm, and the content of the surface modified functional group amino group is 0.3wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-4 is 2.7mmol / g, and the CO2 selectivity is greater than 97%.
[0070] Example 5
[0071] (1) 15 g of ZIF-8 and 15 g of polystyrene (weight average molecular weight of 50,000 g / mol) were mixed to obtain a mixed material;
[0072] (2) transferring the above mixed material to a high temperature furnace, performing heat treatment in a nitrogen atmosphere, controlling the nitrogen flow rate to 50 mL / min, raising the temperature to 500° C., and reacting at a constant temperature for 4 h to obtain a MOFs and porous carbon composite;
[0073] (3) The prepared composite was surface modified by introducing a mixed gas containing 0.5 wt% ammonia, and then kept warm at 500°C for 4 h and cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-5.
[0074] It has been determined that the specific surface area of MOF-5 is 800m 2 / g, the average pore size is 0.5nm, and the content of the surface modified functional group amino group is 0.3wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-5 is 2.5mmol / g, and the CO2 selectivity is greater than 95%.
[0075] Example 6
[0076] (1) 15 g of ZIF-8 and 25 g of polystyrene (weight average molecular weight of 50,000 g / mol) were mixed to obtain a mixed material;
[0077] (2) transferring the above mixed materials into a high temperature furnace, performing heat treatment in a nitrogen atmosphere, controlling the nitrogen flow rate at 50 mL / min, raising the temperature to 400° C., and reacting at a constant temperature for 5 h to obtain a MOFs and porous carbon composite;
[0078] (3) The prepared composite was surface modified by introducing a mixed gas containing 0.5 wt% ammonia, and then kept warm at 400°C for 4 hours and then cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-6.
[0079] It has been determined that the specific surface area of MOF-6 is 1000m 2 / g, the average pore size is 0.4nm, and the content of surface modified functional group amino is 0.2wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-6 is 2mmol / g, and the CO2 selectivity is greater than 90%.
[0080] Example 7
[0081] (1) 15 g of ZIF-8 and 18 g of polystyrene (weight average molecular weight of 50,000 g / mol) were mixed to obtain a mixed material;
[0082] (2) transferring the mixed material to a high temperature furnace, performing heat treatment in a nitrogen atmosphere, controlling the nitrogen flow rate to 50 mL / min, raising the temperature to 550° C., and reacting at a constant temperature for 2 h to obtain a MOFs and porous carbon composite;
[0083] (3) The prepared composite was surface modified by introducing a mixed gas containing 0.5 wt% ammonia, and then kept warm at 550°C for 3 h and cooled to room temperature to obtain a surface-modified MOFs and porous carbon composite material, which was recorded as MOF-7.
[0084] It has been determined that the specific surface area of MOF-7 is 700m 2 / g, the average pore size is 0.6nm, and the content of the surface modified functional group amino group is 0.1wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-7 is 1.5mmol / g, and the CO2 selectivity is greater than 92%.
[0085] Comparative Example 1
[0086] The preparation method of Example 1 is followed, with the only difference from Example 1 being that polystyrene is not added in step (1); and finally a surface-modified MOFs and porous carbon composite material is obtained, which is denoted as MOF-8.
[0087] The specific surface area of MOF-8 is 550m 2 / g, the average pore size is 0.2nm, and the content of the surface modified functional group amino group is 0.1wt%. Under the conditions of 298K and 1atm, the CO2 adsorption capacity of MOF-8 is 1.3mmol / g, and the CO2 selectivity is greater than 82%.
[0088] Comparative Example 2
[0089] The preparation method of Example 1 was followed, except that no surface modification was performed. The other steps were the same as those in Example 1, and finally a MOFs and porous carbon composite was obtained, which was recorded as MOF-9.
[0090] The specific surface area of MOF-9 is 1240m 2 / g, the average pore size is 0.6nm. At 298K and 1atm, the CO2 adsorption capacity of MOF-9 is 1.2mmol / g, and the CO2 selectivity is greater than 75%.
[0091] It can be seen from the above results that the MOFs and porous carbon composite materials prepared by the present invention have high adsorption capacity and selectivity. It can be seen from Examples 1-7 that the mass ratio of MOFs and polystyrene is controlled within the range specified by the present invention, and the composite material obtained has a higher adsorption capacity and greater adsorption selectivity, and is better for adsorbing CO2; no polystyrene is added in Comparative Example 1, resulting in a smaller specific surface area and pore size of the ZIF-8 porous carbon material, a lower adsorption amount, and poor adsorption selectivity; Comparative Example 2 is not subjected to surface modification treatment, and the obtained MOFs and porous carbon composites have a lower adsorption amount and adsorption selectivity for CO2. The effect of the present invention can only be achieved by controlling the mass ratio of ZIF-8 and polystyrene within the range specified by the present invention and satisfying the conditions of heat treatment and surface modification treatment.
[0092] The MOFs and porous carbon composite materials described in the present invention have a high specific surface area, a high adsorption capacity and high selectivity for CO2, can be recycled and have high stability, and the preparation process is simple, the product does not need to be washed again, and the economic benefit is high.
[0093] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A MOFs and porous carbon composite material, characterized in that: The composite material comprises a metal organic framework material and porous carbon combined in the metal organic framework material; the metal organic framework material is ZIF-8; and the mass ratio of the metal organic framework material to the porous carbon is 1:0.5-2.
2. The composite material according to claim 1, wherein The composite material has an average pore size of 0.2-0.5 nm and a specific surface area of 800-1200 m 2 / g.
3. The composite material according to claim 1 or 2, wherein: The composite material also contains modified functional groups attached to the metal organic framework material and the porous carbon surface; Preferably, the modified functional group is selected from at least one of a hydroxyl group, an amino group and a carbonyl group; Preferably, in the composite material, the content of the modified functional group is 0.1-0.5 wt %.
4. The composite material according to any one of claims 1 to 3, wherein: The pore size of ZIF-8 is 0.34-0.36 nm, the average particle size is 10-100 nm, and the specific surface area is 1200-1600 m 2 / g.
5. A method for preparing a MOFs and porous carbon composite material, characterized in that: The method includes: (1) mixing a metal organic framework material and a porous carbon precursor to obtain a mixed material; (2) heat treating the mixed material to obtain a MOFs and porous carbon composite; (3) The composite is subjected to surface modification treatment to obtain a MOFs and porous carbon composite material.
6. The preparation method according to claim 5, characterized in that: In step (1), the mass ratio of the metal organic framework material to the porous carbon precursor is 1:0.5-2; Preferably, the porous carbon precursor is polystyrene; Preferably, the weight average molecular weight of the polystyrene is 30000-80000 g / mol; Preferably, the metal organic framework material is ZIF-8; Preferably, the pore size of ZIF-8 is 0.34-0.36 nm, the average particle size is 10-100 nm, and the specific surface area is 1200-1600 m 2 / g.
7. The preparation method according to claim 5, characterized in that: In step (2), the heat treatment is carried out in the presence of a protective gas, wherein the protective gas is preferably nitrogen, and the nitrogen gas flow rate is 50-80 mL / min; Preferably, the target temperature of the heat treatment is 400-600° C., and the holding time is 2-6 hours.
8. The preparation method according to claim 5, characterized in that: In step (3), the surface modification process comprises: keeping the composite at the target temperature for 2-5 hours in the presence of hydrofluoric acid or a mixed gas containing ammonia; Preferably, the concentration of the hydrofluoric acid is 10-20wt%; Preferably, the mixed gas includes ammonia and nitrogen; Preferably, the concentration of ammonia in the mixed gas is 0.5-1 wt %.
9. The MOFs and porous carbon composite material obtained by the preparation method according to any one of claims 5 to 8.
10. Application of the MOFs and porous carbon composite material according to any one of claims 1 to 4 and 9 in the technology of capturing carbon dioxide in flue gas.
Citation Information
Patent Citations
Methods of applying a sorbent coating on a substrate, a support, and / or a substrate coated with a support
CN103958027A
Composite carbon dioxide adsorption material, preparation method and application thereof
CN104056599A
Method for preparing MIL-100Al-based porous carbon material for carbon dioxide adsorption and separation
CN106563415A
Catalyst for preparing unsaturated carbonate as well as preparation method and application of catalyst
CN116020560A
Amine-based porous polymer for selective carbon dioxide capture
US20200239617A1